SFB754 Autonomous glider data - Gerd Krahmann; Hela Mehrtens (PANGAEA, 2021)
Autonomous gliders were deployed during several cruises but also as stand-alone missions independent from large research vessels (see Table C5). Two different generations of Teledyne Webb Research Slocum gliders were used, G1 and G2. All gliders were equipped with Seabird CTD systems, G1 gliders with an unpumped and G2 gliders with a pumped version, respectively. An Aanderaa optode was present on all gliders to observe dissolved oxygen concentrations. Optical fluorescence and backscatter sensors manufactured by Wetlabs were also present on all gliders albeit in different configurations. They allowed the determination of CHL-a (excitation and emission wavelengths of 470 and 695 nm, respectively) and CDOM (excitation and emission wavelengths of 370 and 460 nm, respectively) concentrations and the turbidity (scattering wavelength of 470 nm) of the waters. All glider data was processed using a GEOMAR-developed software (Thomsen et al., 2016) resulting in gridded fields for all observed variables. During a small number of glider deployments, a Seabird/Satlantic SUNA Nitrate sensor was attached to a glider. SUNA data was again processed following the procedures outlined in Sakamoto et al. (2009) and Sakamoto et al. (2017) and calibrated against Nitrate measurements from nearby CTDO casts with discrete Nitrate measurements. Microstructure sensors were also attached to gliders on several deployments (see the following section).